Regulation of tetrapyrrole synthesis by light in chemostat cultures of Rhodobacter sphaeroides. - Oelze, J (1988)
Control of bacteriochlorophyll (Bchl), magnesium protoporphyrin monomethyl ester (MgPME), cytochromes, and coproporphyrin by light was studied with chemostat cultures of Rhodobacter sphaeroides growing at a constant dilution rate. By increasing the growth-limiting light energy flux from 10 to 55 W/m2, specific Bchl contents decreased from 19.3 to 7.9 nmol/mg of protein. This was strictly proportional to a decrease in the ratio of B800-850 to B875 light-harvesting complexes. MgPME levels increased from 1.5 to 5.3 nmol/mg of protein, while cytochrome as well as coproporphyrin levels stayed constant at 0.46 and 1.95 nmol/mg of protein, respectively. Since in chemostat cultures steady-state levels of a product represent the rate of synthesis, these results infer only slight control of the rate-limiting step of total tetrapyrrol formation by light. In substrate-limited cultures MgPME was accumulated when growth and Bchl formation approached substrate saturation. This suggests that light controls a second step, i.e., MgPME conversion, whenever too much precursor is available, owing to the low sensitivity of the initial step of control. MgPME was preferentially localized in a subcellular fraction with high contents of B875 complexes. A second fraction exhibiting increased contents of B800-850 complexes lacked significant levels of MgPME. These results are discussed in terms of localization of Bchl synthesis in the membrane system of R. sphaeroides.